INTEGRASI PENDIDIKAN ANTI NARKOBA DALAM PEMBELAJARAN TEMATIK KURIKULUM 2013 DI SEKOLAH DASAR - Faisal ,dkk (JURNAL KELUARGA SEHAT SEJAHTERA, 2016)
This article aims to describe the integration of anti-drug education in thematic learning curriculum, 2013 in SD. The integration of character education is an anti-drug education program that conceptually allows pasted in the learning process that is already in school. This program can be done in the form of expansion of existing themes in the curriculum by using a contextual approach to anti-drug learning. Integration of anti-drug education in thematic learning, is one of the efforts to create students who have the knowledge, attitudes, and skills are balanced in accordance with the mandate of the curriculum in 2013.Kata Kunci: Anti Narkoba, Pembelajaran Tematik, Kurikulum 2013, SD